Genome-wide association studies provide genetic insights into natural variation of seed-size-related traits in mungbean - Liu, Jinyang; Lin, Yun; Chen, Jingbin; Yan, Qiang; Xue, Chenchen; Wu, Ranran; Chen, Xin; Yuan, Xingxing (Frontiers in Plant Science, 2022)
Although mungbean (Vigna radiata (L.) R. Wilczek) is an important legume crop, its seed yield is relatively low. To address this issue, here 196 accessions with 3,607,508 SNPs were used to identify quantitative trait nucleotides (QTNs), QTN-by-environment interactions (QEIs), and candidate genes for seed length, seed width, and 100-seed weight in two environments using several methods. As a result, 98 QTNs and 20 QEIs were identified using 3VmrMLM, while 95, >10,000, and 15 QTNs were identified using EMMAX, GEMMA, and CMLM, respectively. Among 809 genes around these QTNs, 12 were homologous to known seed-development genes in rice and Arabidopsis thaliana, and 10, 2, 1, and 0 were found, respectively, by the above four methods to be associated with the three traits, such as VrEmp24/25 for seed length and VrKIX8 for 100-seed weight. Eight of the twelve genes were significantly differentially expressed between two large-seed accessions and two small-seed accessions, and VrKIX8, VrPAT14, VrEmp24/25, VrIAR1, VrBEE3, VrSUC4, and Vrflo2 were further verified by RT-qPCR. Among 65 genes around these QEIs, VrFATB, VrGSO1, VrLACS2, and VrPAT14 were homologous to known seed-development genes in Arabidopsis thaliana, although new experiments are necessary to explore these novel GEI-trait associations. In addition, 54 genes were identified in comparative genomics analysis to be associated with seed development pathway, and VrKIX8, VrABA2, VrABI5, VrSHB1, and VrIKU2 were also identified in genome-wide association studies. This result provided a reliable approach for identifying seed-size-related genes in mungbean and a solid foundation for further molecular biology research on seed-size-related genes.